Decolourization of selected textile dyes by white rot fungus Coriolopsis sp. strain AFF17 - Cheng, Wei Nee (2014)
Synthetic dyes are replacing natural dyes in modern textile industries. However, each year, about 10% of dyestuffs wastes enter to the environment and causes water pollution. As synthetic dyes are designed to resist fading therefore they are recalcitrant in the environment. Since physicochemical treatments have limited efficiency and disadvantages, bioremediation of dyestuffs wastes with microorganisms is gaining scientific interest as an alternative pollution treatment. A previously locally isolated white rot fungus,Coriolopsis sp. Strain aff17 (EU863193) from UPM, Serdang was screened for its ability to decolourize azo dyes. It was able to decolourize eleven out of thirteen azo dyes that were chosen. Only seven azo dyes were used in the studies namely Ponceau 2R (C.I. 20470), Amaranth (C.I. 16185), Orange G (C.I. 16230), Naphthol Blue Black (C.I. 20470), Remazol Black B (C.I. 20505), Trypan Blue (C.I. 23850) and Sirius Light Blue BRR (C.I. 34140). Charcaterizations of decolourization ability by Coriolopsis sp. Strain aff17 were investigated. Decolourization rates were shown to be higher in shake cultures as compared to static cultures. The best agitating speed for decolourization of dyes was found to be 75 rpm. The best medium for the decolourization of dyes was distilled water. The presence of chromium, arsenic, cadmium and lead did not inhibit the decolourization of by Coriolopsis sp. Strain aff17, but slightly increase the decolourization process even at a high concentration of 2.0 mg/L. Copper which is essential for laccase, surprisingly showed lower down the decolourization at the concentration above 1.5 mg/L. Mercury inhibited the decolourization even at a low concentration of 0.5 mg/L. The detection of LMEs was studied in 1L and 2L conical flasks. Larger surface area was shown to have a better decolourization rate when 500 mL of working volume was placed into both 2L flask and 1L flask. Two Litre flask’s culture has a larger surface area providing more contact with air therefore providing a better condition for dye decolourization. Laccase and Manganese peroxidase were found in Coriolopsis sp. Strain aff17. These Lignin Modifying Enzymes’ activities show inverse relationship to the concentration of azo dye. Coriolopsis sp. Strain aff17 was grown on agricultural wastes such as sugarcane bagasse, sugarcane peel and paddy straw, to serve as the alternative inoculum in the 2L decolourizing system to replace the utilization of Potato Dextrose Broth. Coriolopsis sp. Strain aff17 that was grown on paddy straw showed the fastest decolourization, which was six days, followed by sugarcane peels (eight days) and sugarcane bagasse (twelve days). Coriolopsis sp. Strain aff17 was then tested on raw wastewaters that were collected from rivers near textile factories of Pahang, Malaysia, to further study its ability to decolourize raw wastewater. Coriolopsis sp. Strain aff17 was able to decolourize limited raw wastewater without addition of glucose by 12.74 to 24.89%. However with the addition of glucose, the decolourization percentage can reach over 84%. In conclusion, Coriolopsis sp. Strain aff17 is proven to be able to decolourize various azo dyes. More studies should be continued to determine if Coriolopsis sp. Strain aff17 is able to decolourize dyes in harsher conditions found in raw wastewater. Coriolopsis sp. Strain aff17 also should be tested on other pollutants.